2020
DOI: 10.3390/biomedicines8120583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Histamine Receptor Antagonist Cetirizine on Orthodontic Tooth Movement

Abstract: Many patients regularly take histamine receptor antagonists, such as cetirizine, to prevent allergic reactions, but these antiallergic drugs may have inadvertent effects on orthodontic treatment. In previous studies, histamine has been shown to modulate the sterile inflammatory reaction underlying orthodontic tooth movement. Pertinent effects of histamine antagonization via cetirizine during orthodontic treatment, however, have not been adequately investigated. We thus treated male Fischer344 rats either with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The extracted right incisors of Rabbits #3, #4, #5, #6 and #7 were immersed in an EDTA decalcifying solution (Sangon Biotech, Shanghai, China) [36]. After rinsing for 5 min with running water, the samples were dehydrated and embedded in paraffin (Xiya Reagent, Linyi, Shandong, China).…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…The extracted right incisors of Rabbits #3, #4, #5, #6 and #7 were immersed in an EDTA decalcifying solution (Sangon Biotech, Shanghai, China) [36]. After rinsing for 5 min with running water, the samples were dehydrated and embedded in paraffin (Xiya Reagent, Linyi, Shandong, China).…”
Section: Hematoxylin and Eosin Stainingmentioning
confidence: 99%
“…All results showed that force-tested groups have a significantly higher risk of OIIRR than the no-force control groups ( 92 , 93 , 94 , 95 , 91 , 96 , 97 , 98 , 99 , 100 , 10 , 2 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ). Only one study reported no significant difference in OIIRR between the intermittent force and control Groups ( 103 ).…”
Section: Resultsmentioning
confidence: 94%
“…Only one study reported no significant difference in OIIRR between the intermittent force and control Groups ( 103 ). Eight studies had data for the secondary outcomes; histological and molecular findings ( 91 , 100 , 10 , 101 , 2 , 102 , 104 , 106 ). The summaries of the included studies are listed in Supplementary Table 9 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sperl et al [9] hypothesized that many patients, to prevent allergic reactions, regularly use histamine receptor antagonists, such as cetirizine. However, these may have adverse effects on orthodontic treatment.…”
mentioning
confidence: 99%